Starting the fight in the tumor: expert recommendations for the development of human intratumoral immunotherapy (HIT-IT). (8th October 2018) - Marabelle, A; Andtbacka, R; Harrington, K; Melero, I; Leidner, R; de Baere, T; Robert, C; Ascierto, P A; Baurain, J -F; Imperiale, M; Rahimian, S; Tersago, D; et al.
Abstract: A European Society for Medical Oncology (ESMO)-sponsored expert meeting was held in Paris on 8 March 2018 which comprised 11 experts from academia, 11 experts from the pharmaceutical industry and 2 clinicians who were representatives of ESMO. The focus of the meeting was exclusively on the intratumoral injection/delivery of immunostimulatory agents with the aim of harmonizing the standard terms and methodologies used in the reporting of human intratumoral immunotherapy (HIT-IT) clinical trials to ensure quality assurance and avoid a blurring of the data reported from different studies. The goal was to provide a reference document, endorsed by the panel members that could provide guidance to clinical investigators, pharmaceutical companies, ethics committees, independent review boards, patient advocates and the regulatory authorities and promote an increase in the number and quality of HIT-IT clinical trials in the future. Particular emphasis was placed not only on the development of precise definitions to facilitate a better understanding between investigators but also on the importance of systematic serial biopsies as a driver for translational research and the need for the recording and reporting of data, to facilitate a better understanding of the key processes involved.